High potency STING agonists engage unique myeloid pathways to reverse pancreatic cancer immune privilege. Issue 8 (2nd August 2021) - Ager, Casey R; Boda, Akash; Rajapakshe, Kimal; Lea, Spencer Thomas; Di Francesco, Maria Emilia; Jayaprakash, Priyamvada; Slay, Ravaen B; Morrow, Brittany; Prasad, Rishika; Dean, Meghan A; Duffy, Colm R; Coarfa, Cristian; et al.
Abstract : Background: Intratumoral injection of cyclic dinucleotide (CDN) agonists of the stimulator of interferon genes (STING) pathway engages innate immune activation and priming of adaptive immune effectors to foster local and distal tumor clearance. Despite proven therapeutic efficacy in preclinical models, a thorough understanding of how CDNs reprogram suppressive myeloid stroma in mouse and man is lacking. Methods: Here, we perform deep transcript-level and protein-level profiling of myeloid-derived suppressor cells and M2 macrophages following stimulation with CDNs of ascending potency. Additionally, we leverage orthotopic Kras +/G12D TP53 +/R172H Pdx1-Cre (KPC) derived models of pancreatic adenocarcinoma (PDAC) to determine the capacity for locally administered CDNs to sensitize PDAC to immune checkpoint blockade. We use bioluminescent in vivo imaging and 30-parameter flow cytometry to profile growth kinetics and remodeling of the tumor stroma post-therapy. Results: Highly potent synthetic STING agonists repolarize suppressive myeloid populations of human and murine origin in part through inhibition of Myc signaling, metabolic modulation, and antagonism of cell cycle. Surprisingly, high-potency synthetic agonists engage qualitatively unique pathways as compared with natural CDNs. Consistent with our mechanistic observations, we find that intratumoral injection of the highest activity STING agonist, IACS-8803, into orthotopic pancreatic adenocarcinoma lesions unmasks sensitivity to checkpoint blockade immunotherapy. Dimensionality reduction analyses of high parameter flow cytometry data reveals substantial contributions of both myeloid repolarization and T cell activation underlying the in vivo therapeutic benefit of this approach. Conclusions: This study defines the molecular basis of STING-mediated myeloid reprogramming, revealing previously unappreciated and qualitatively unique pathways engaged by CDNs of ascending potency during functional repolarization. Furthermore, we demonstrate the potential for high potency CDNs to overcome immunotherapy resistance in an orthotopic, multifocal model of PDAC.